The transnational frontier of resort master plans: a gateway to borderless legacies for the environment and humanity - Ayala, Hana (Frontiers in Environmental Economics, 2024)
The article departs from the evolving concept and practice of the tourism and hotel industry's environmental stewardship, with a special emphasis on the industry's initiatives inspired by the latest United Nations' agreements to tackle global warming and reverse biodiversity loss. It singles out the international resort enterprise for its unmatched yet dormant potential to deliver transformational insights into borders-blind linkages and relationships shaped by evolutionary and ecological forces and interwoven in the marvel and fragility of our living planet. This move is corroborated with analyses of the latent economic power of wonder embedded in the natural world's infinite connectivity and is emboldened in its promise via comparisons with the ever-grander ambition of science philanthropy and eco-philanthropy. The article makes the case and supplies a blueprint for a new generation of resort products and resort portfolios master-planned to shepherd and sustain through their business model transnational routes of awareness and guardianship of "one Earth" and to facilitate science-charted recalibration of global conservation strategies.